Casos y cosas: semanario popular (Vol. 2, No. 51) - Imprenta La Region (My University, 1920)
SPANISH: Incluye: Ya era tiempo, De todo un poco, Sigue la farsa?, Un policía, satiro?, La ola de pereza, Ya llegó...., Las solteras y el aeropuerto, Y los suponemos atrasados, Léase "La Región", Lo que piensa Fray Candil

ENGLISH: It's about time, a little bit of everything, The farce continues, A policeman, a satyr, The wave of laziness has arrived...., The bachelorettes and the airport, And we assume the backward, Read "The Region", What Fray Candil thinks
Cases and things: popular weekly (Vol. 2, No. 51)
Keywords: Periodicals; Satire, Peruvian; Humor; Iquitos (Perú)--revistas; Perú--revistas satíricas